Portable Security Locker Using IoT - Nur Hakim, Muhammad; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2024)
Everybody possesses important possessions, such as a passport, wallet, credit card, and smartphone. Losing them as a result of theft or robbery may result in the loss of personal information, financial data, or money. When travelling abroad, losing valuables is even worse because it involves dealing with authorities that the traveler is unfamiliar with. Therefore, a Portable Security Locker using Internet of Things (IoT) is proposed to overcome the problems of misplacing important belongings or losing them due to theft or robbery. The Locker is equipped with RFID module, fingerprint scanner, keypad password, alarm and GPS tracker for increased security purposes. A message that indicates whether the RFID tag is matched or not will appear on the OLED display as soon as the RFID tag is read by the RFID reader. The user must then scan their fingerprint on the fingerprint scanner if the tag matches. The user may attempt numerous times if it is not matched, though. The user must scan his fingerprint on the scanner in order to use the next level security system. The user may not attempt this level more than three times. In the event that this does not happen, countermeasures will be taken, including the activation of an alarm and GPS tracker, which will result in alert messages being sent to user’s email and WhatsApp application. The user’s mobile phone’s ThingSpeak application makes it simple to find the location of the security locker in the event of theft or robbery. The user will be able to move on to the keypad password system at the top security level if their fingerprints match. Similar countermeasures as in the second level security system shall be used if the user attempted more than three times. The locker’s location on ThingSpeak application has been compared to its location on Google Maps, and the results show a good agreement. In conclusion, the level of security offered by this portable security locker is sufficient to fend off theft and robbery.